Use of Moringa Leaves to Meet Toddler Nutrition in The Prevention of Stunting - Zelda Nora Afriza; Nova Muhani; Nurhalina Sari; Fitri Eka Sari (Postgraduate, University of Mataram, 2023)
In 2017, 43.2% of children under five in Indonesia had an energy deficit and 28.5% had a mild deficit. For protein adequacy, 31.9% of toddlers experienced a protein deficit and 14.5% experienced a mild deficit. The high prevalence of stunting is a priority that must be resolved with local food sources that are abundant and high in nutritional content, namely moringa leaves. Moringa leaves have high nutritional content and are easily available in the surrounding environment, but are still very diverse in their utilization. The purpose of this study was to determine the factors associated with the utilization of moringa leaves by mothers of toddlers in preventing stunting in Sumber Rejo Village. This study is a quantitative study with a Cross Sectional design with a population and sample size of 120 respondents with total sampling technique and univariate and bivariate analysis tests using Chi Square. Respondents who had insufficient knowledge were 13.3%, respondents who had a negative attitude were 43.3%, respondents who did not have moringa availability were 23.3% and respondents who had a moringa consumption pattern were 11.7% and respondents who did not utilize moringa leaves were 40%. There is a relationship between knowledge (p-value 0.039), attitude (p-value 0.000), moringa availability (p-value 0.034) and moringa consumption patterns (p-value 0.000) with the utilization of moringa by mothers of toddlers in preventing stunting in Sumber Rejo Village. It is hoped that health workers will conduct education or counseling for mothers of toddlers to increase the knowledge of mothers of toddlers about the use of moringa and it is hoped that mothers will improve moringa consumption patterns for toddlers and families with various variations of moringa preparations in order to increase the utilization of moringa as food intake for stunting prevention.